The locked room : a Martin Beck novel - Sjowall, Maj (Martin Beck, 2011)
In one part of town, a woman robs a bank. In another, a corpse is found shot through the heart in a room locked from within, with no firearm in sight.Although the two incidents appear unrelated, Detective Inspector Martin Beck believes otherwise, and solving the mystery acquires the utmost importance.